Chronologics Periodisation in a Global Context - Mittler, Barbara; Maissen, Thomas; Monnet, Pierre (Heidelberg University Publishing (heiUP), 2022)
Many contemporary periodisation schemes have their roots in Europe, reflecting particular national religious or historiographical traditions and teleologies. As part of the colonial encounter they have been translated into new temporal authenticities in the Americas, Asia and Africa. Culturally determined as they are, these periodisation schemes are begging for systematic comparison in order to identify their contextual specificity and contingency. An interdisciplinary and transregional approach allows to work out categories of historical analysis that go beyond nation-bound interpretative patterns. In considering case studies from different parts of the world, the aim of this volume is to uncover some of the dynamics behind particular uses of periodisation schemes, as concepts for ordering the past.